An aerodynamic anti-galloping technique of iced 8-bundled conductors in ultra-high-voltage transmission lines. Issue 193 (October 2019) - Lou, Wenjuan; Huang, Cirong; Huang, Mingfeng; Yu, Jiang
Abstract: Galloping of iced conductors is a kind of self-excited aeroelastic vibration with low frequency and large amplitude causing various damages on transmission tower-line systems. A newly designed galloping simulation device is employed in the wind tunnel for developing an aerodynamic anti-galloping technique of iced 8-bundled conductors in ultra-high-voltage (UHV) transmission lines. The anti-galloping technique is based on the proposed rotary clamp spacers, which allow the connected sub-conductors to rotate around its axis. Iced 8-bundled conductor models of UHV lines with and without twistable sub-conductors have been tested in the wind tunnel under various wind attack angles and five different ratios of vertical vibration frequency over the torsional. Aerodynamic damping ratios were identified from measured response data, and were used as indicators of galloping for iced 8-bundled conductor models with and without twistable sub-conductors. Equations of motion for iced 8-bundled conductors with and without twistable sub-conductors are respectively established, and the aerodynamic instability of the system can then be predicted by solving the eigenvalue problem associated with equations of motion. In order to further validate the anti-galloping effects of the rotary clamp spacers, finite element simulation has been conducted for a real UHV transmission line with a span of 500 m located in the galloping-prone area. Highlights: A newly designed galloping simulation device is tested in the wind tunnel. The anti-galloping technique based on the rotary clamp spacers is experimentally validated and optimized. Numerical simulation of the rotary clamp spacers has been implemented. 7DOF coupled model for galloping was developed.